TRANSFORMATION POTENTIAL OF SMALL PROSE IN THE HISTORIC AND LITERARY PROCESS (BASED ON THE MATERIAL OF ARTISTIC WORK BY VASYL STEFANYK) - Golod, N. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article is dedicated to the historic and theoretic literary analysis of the works of Ukrainian and foreign researchers, that studied the problem of transformation potential of the small prose genres in the synchronic and diachronic aspects. A review is made of the main approaches towards studying the problem of the kinship of a short story with epic and dramatic kin of literature. It has been found out: the majority of the researchers think that the typology of genres according to their kin has been sustained only in classicism with its demand for purity and canonicity of the literary forms, and in such literary streams like romanticism, realism, modernism, the genres emerge on the crossing of lyrics, epos and drama. Practically all of the researchers of the short story point out the concentration and laconicity of the genre of short story. This feature is usually connected to the manifestation of the dramatization in the epic genre as a whole. The substance of life in the end of XIX - at the beginning of the XX centuries is characterized by the acceleration of the civilized progress as well as by the intensifying of the time and space bonds, both in Ukraine and the World. These processes are determined by the change in the social and economic formations, accomplishments of the scientific and technical progress, development and achievements in the natural and technical branches of scientific knowledge, postulates of the philosophy of positivism, etc. Therefore, a concentration has been reflected in the peculiarities of the then spiritual, cultural and literary life. Under such circumstances the small prose, and short stories in particular, turned out to be the most operative and productive "content form". The success of Ukrainian small prose of the mentioned period to a great extend has been triggered both by the dialectic unity of the traditions and novelty of the national literary process, and the subjective conditions connected with the talent of the representatives of letters as well as the flexibility, experimental nature and an inclination to transformation by the leading genres of small prose. So in the article, a conclusion is made about the resonance between the novelty attempt of an individual artistic method of Vasyl Stefanyk and the transformation potential of short story as a genre.